2010
DOI: 10.1088/1748-6041/5/6/062001
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells in bone tissue engineering

Abstract: Bone tissue engineering has been one of the most promising areas of research, providing a potential clinical application to cure bone defects. Recently, various stem cells including embryonic stem cells (ESCs), bone marrow-derived mesenchymal stem cells (BM-MSCs), umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs), adipose tissue-derived stem cells (ADSCs), muscle-derived stem cells (MDSCs) and dental pulp stem cells (DPSCs) have received extensive attention in the field of bone tissue engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
150
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 133 publications
2
150
0
7
Order By: Relevance
“…Meanwhile, bone marrow MSCs are multipotent cells that have been considered as ideal seed cells in the bone repair. 49 Therefore, the aim in the present study was to evaluate the cell response of obtained PEG/PLA electrospun hybrid scaffolds to MSCs, and the osteogenic development behavior of MSCs cultured on the PEG/PLA electrospun fibrous scaffold in vitro. Surrounding tissue response to the fibrous scaffolds in vivo was also evaluated by transplanting the PEG/PLA electrospun hybrid scaffold into the thigh muscle pouches of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, bone marrow MSCs are multipotent cells that have been considered as ideal seed cells in the bone repair. 49 Therefore, the aim in the present study was to evaluate the cell response of obtained PEG/PLA electrospun hybrid scaffolds to MSCs, and the osteogenic development behavior of MSCs cultured on the PEG/PLA electrospun fibrous scaffold in vitro. Surrounding tissue response to the fibrous scaffolds in vivo was also evaluated by transplanting the PEG/PLA electrospun hybrid scaffold into the thigh muscle pouches of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of growth factors and hormones, such as transform growth factor beta (TGF-β), fibroblast growth factor (FGF), insulin-like growth factor 1 (IGF-1), bone morphogenetic protein (BMP) and parathormone (PTH), on MSCs proliferation and differentiation have been studied thoroughly (Haddad and Harb 2005;Qi et al 2009;Huang et al 2010). It has been reported that MSCs cultured in vitro would differentiate into osteoblasts spontaneously (Seong et al 2010;Mikami et al 2011). But whether HIF-1α and Cbfα1 are involved in the proliferation and differentiation of MSCs as well as the osteogenesis-like changes under hypoxia has not been revealed, and also little is known about the regulation of Cbfα1 during the differentiation of MSCs into osteogenic lineage cells.…”
mentioning
confidence: 99%
“…BMPs belong to the transforming growth factor-beta (TGF-β) superfamily of polypeptides, including TGF-β, activins/inhibins, and BMPs. Specifically, BMP-2 has been demonstrated to induce the differentiation of ADSCs into osteocytes, promote osteogenic differentiation, upregulate bone gene expression after mechanical injury, and improve bone repair after injury (Seong et al, 2010). BMPs bind to specific transmembrane type I and type II receptors and stimulate the intracellular mediators Smad-1, -5, and -8 (Herpin and Cunningham, 2007), which transmit the BMP signal into the nucleus to regulate target gene transcription (Lian et al, 2006).…”
Section: Discussionmentioning
confidence: 99%